Exoplanetary atmosphere target selection in the era of comparative planetology - J. S. Morgan (2020)
© 2019 The Author(s). The large number of new planets expected from wide-area transit surveys means that follow-up transmission spectroscopy studies of their atmospheres will be limited by the availability of telescope assets. We argue that telescopes covering a broad range of apertures will be required, with even 1 m-class instruments providing a potentially important contribution. Survey strategies that employ automated target selection will enable robust population studies. As part of such a strategy, we propose a decision metric to pair the best target to the most suitable telescope, and demonstrate its effectiveness even when only primary transit observables are available. Transmission spectroscopy target selection need not therefore be impeded by the bottle-neck of requiring prior follow-up observations to determine the planet mass. The decision metric can be easily deployed within a distributed heterogeneous network of telescopes equipped to undertake either broad-band photometry or spectroscopy. We show how the metric can be used either to optimize the observing strategy for a given telescope (e.g. choice of filter) or to enable the selection of the best telescope to optimize the overall sample size. Our decision metric can also provide the basis for a selection function to help evaluate the statistical completeness of follow-up transmission spectroscopy data sets. Finally, we validate our metric by comparing its ranked set of targets against lists of planets that have had their atmospheres successfully probed, and against some existing prioritized exoplanet lists.